2022
DOI: 10.7759/cureus.33066
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Cutaneous Effects of Pornography Addiction: A Narrative Review

Abstract: Pornography addiction is an area of increasing concern, particularly due to the ubiquitous nature of pornographic material on the Internet. Even so, there is no formal Diagnostic and Statistical Manual of Mental Disorders (DSM-5) inclusion of compulsive pornography use as a behavioral addiction. Although the psychosocial impacts of pornography addiction have been studied, the risk of direct skin injuries and behavioral changes brought about by excessive pornography usage remain to be seen. Adult males constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…This imitation might contribute to the likelihood of early sexual activity and the transmission of diseases that are transmitted sexually. Several studies have reported a correlation between masturbation and skin manifestations; however, the strength of this connection remains unclear (7). Adolescents who engage in pornography, particularly through online platforms, exhibit elevated levels of delinquent conduct, an increased prevalence of depressive symptoms, and a diminished sense of emotional attachment to their caregivers (8).…”
Section: Introductionmentioning
confidence: 99%
“…This imitation might contribute to the likelihood of early sexual activity and the transmission of diseases that are transmitted sexually. Several studies have reported a correlation between masturbation and skin manifestations; however, the strength of this connection remains unclear (7). Adolescents who engage in pornography, particularly through online platforms, exhibit elevated levels of delinquent conduct, an increased prevalence of depressive symptoms, and a diminished sense of emotional attachment to their caregivers (8).…”
Section: Introductionmentioning
confidence: 99%